Factors contributing to school food program acceptance: a Review of Canadian literature. (18th February 2023) - Everitt, Tracy; Ward, Stephanie; Martin, Wanda; Engler-Stringer, Rachel
Abstract: Diet quality and food security are a concern in school-aged children in Canada. In 2019, the Canadian federal government announced the intention to work towards a national school food program. Understanding the factors that impact school food program acceptability can inform planning to ensure that students are willing to participate. A scoping review of school food programs in Canada completed in 2019 identified 17 peer-reviewed and 18 grey literature publications. Of these, five peer-reviewed and nine grey literature publications included a discussion of factors that impact the acceptance of school food programs. These factors were thematically analyzed into categories: stigmatization, communication, food choice and cultural considerations, administration, location and timing, and social considerations. Considering these factors while planning can help to maximize program acceptability. Lay Summary: Diet quality and having sufficient food to eat are concerns in school-aged children in Canada. In 2019, the Canadian federal government announced the intention to work towards a national school food program. Providing food to children in schools can only address diet concerns if children participate. Understanding the factors that impact school food program acceptability can inform planning to contribute to program acceptance. Themes of factors contributing to school food program acceptance discussed in 14 publications were identified. Themes included stigmatization, communication, food choice and cultural considerations, administration, location and timing, and social considerations. Considering these factors while planning can help to maximize school food program acceptability.